(untitled) (Texas Journal of Medical Science, 2023)
We observed 85 patients aged 17 to 74 years. All patients used standard general, serological, biochemical and statistical methods. According to clinical forms patients were distributed as follows: primary chronic brucellosis (PChB) - 22 (25.8%) and secondary chronic brucellosis (SChB) - 63 (74.2%). The subcompensation phase was observed in 62.3% of the examined patients, the decompensation phase was detected in 37.7%